Pattern and Use of Yak-cattle Hybridization in Hindu-Kush Himalayas: A Review - Gorkhali, Neena Amatya; Sapkota, Saroj; Dorji, Tashi; Pokharel, Bhoj Raj; Kolakshyapati, Mana Raj; Bhattarai, Nirajan (Journal of Nepal Agricultural Research Council, 2025)
Yak (Bos grunniens) is an iconic animal for the Hindu-Kush Himalayan (HKH) regions of Central Asia and is an important source of food security and means of livelihood for people in this region. At lower elevations, interspecies hybridization between yak and local hill cattle (Bos indicus) is common to combine the yak’s hardiness with the productivity of cattle. In some countries, some researchers have demonstrated successful hybridization of yak with commercial dairy breeds such as Holstein-Friesian (Bos taurus) through artificial insemination to produce improved hybrids to increase milk production. In Bhutan, a unique triple crossing between yak, cattle, and mithun (as a terminal sire) is common for meat production. The hybrids, however, are less adapted to the harsh conditions and high altitudes typical of yak and are kept at intermediate elevations between cattle and yak habitat. So, to produce the best F1 hybrid, it needs to conserve and maintain the best gene pool of both pure Yak and hill cattle, taking care of the economic and biological limits such as reproductive rate and survival rate of Yak. There is circumstantial evidence that some inbreeding is likely to have occurred with yak as a result of traditional pure-breeding methods and, in some countries, because of insufficient interchange of breeding stock across national boundaries. From the review, it can be concluded that the pure yak population should be maintained in the mountain region under community-based selective pure breeding with a defined breeding protocol for genetic improvement. Similarly, to enhance the productivity of hybrid yak cattle, selection in the hill cattle together with pure yak is warranted to get the maternal inheritance in the yak hybrid populations. Introgressive hybridization, however, plays an important role in the improvement of yak management and breeding in an intermediate zone between cattle and yak habitats.